P069 Constitutive overexpression of interleukin 38 has a negative impact on human NHK keratinocyte fitness. (March 2019) - Mermoud, L; Talabot-Ayer, D; Brembilla, N; Julia Borowczyk-Michalowska, J; Palmer, G
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Interleukin (IL)-38 is a member of the IL-1 cytokine family. Based on its sequence homology with the IL-1 and IL-36 receptor antagonists, IL-38 was proposed to act as an anti-inflammatory molecule. However, few data are available to date about its biological role and mechanism of action. Highest constitutive IL-38 expression is detected in the skin, where the cytokine is produced mainly by differentiated keratinocytes. Objectives: The aim of this study is to investigate the function of IL-38 in human keratinocytes, using the immortalized normal human keratinocyte (NHK) cell line stably transfected with vectors allowing for constitutive or inducible IL-38 overexpression. Methods: NHK cell proliferation and mortality were assessed respectively by cell counting and by measuring LDH activity in the supernatant of high density cell culture. Differentiation of NHK cells was initiated by switching to a culture medium containing high Ca ++ and serum. mRNA levels of differentiating NHK cells were determined by RTqPCR. Results: Constitutive IL-38 overexpression reduced the proliferation of NHK cells and lead to increased mortality. Differentiating NHK cells constitutively overexpressing IL-38 had increased mRNA levels for the early differentiation marker keratin 10 as compared to empty vector transfected control cells. On the contrary, expression of the late differentiation marker involucrin was reduced in NHK cells constitutively overexpressing IL-38. To further explore potential effects of IL-38 on keratinocyte differentiation, while circumventing the impact of its constitutive overexpression on cell fitness, we set up a doxycyclin-inducible Tet-On system to overexpress IL-38 in NHK cells. Conclusions: We are currently optimizing 2D and 3D culture conditions for in vitro differentiation of NHK cells to mimic more closely the situation in human skin. We will then study the impact of IL-38 on NHK cell differentiation using cells transfected with the inducible IL-38 expression system. In conclusion, our results suggest that constitutive overexpression of IL-38 decreases proliferation and viability of NHK cells. We will thus use an inducible expression system to further investigate the effects of IL-38 on NHK cells. Disclosure of Interest: None declared.